Gender and information processing in electronic age - Protopsaltis, Aristidis; Bouki, Vassiliki (SIGDOC 2008 - Proceedings of the 26th ACM International Conference on Design of Communication, 2008)
The effect of gender in academic achievement has often been the focus of research because of its potential implications. However, the Web has modified the way people access and use information. The present study examines the differences between males' and females' reading behaviour in hypertexts. The study focuses on text based electronic documents. Ninety participants (27 females and 63 males) read a hierarchically structured hypertext and answered a set of questions. The study examines some original variables not previously studied comprehensively, such as coherence of transactions, sum of selected hyperlinks, hyperlink location etc. The results show that gender did not significantly affect any of the measured variables. The data consisted of reading times, comprehension scores, coherent links, hyperlink location, sum of hyperlinks, and the sum of read nodes. Copyright 2008 ACM.
Created from Fastlane, Scopus look-up
Keywords: Cognitive processes; Coherence; Comprehension; Gender; Hyperlinks; Hypertext; Information processing; Reading